Prevalence of malnutrition and analysis of related factors in elderly patients with COVID-19 in Wuhan, China - Li, Tao; Zhang, Yalan; Gong, Cheng; Wang, Jing; Liu, Bao; Shi, Li; Duan, Jun (European journal of clinical nutrition, 2020)
Background/objectives To evaluate the prevalence of malnutrition and its related factors in elderly patients with COVID-19 in Wuhan, China. Subjects/methods In a cross-sectional study, we evaluated the nutritional status of elderly inpatients with COVID-19 using the Mini Nutritional Assessment (MNA). Based on MNA scores, patients were divided into non-malnutrition group (MNA ≥ 24), the group with risk of malnutrition (MNA 17–23.5) and malnutrition group (MNA score < 17). Regression analysis was conducted to screen for risk factors for malnutrition. Results A total of 182 patients were included in the study, of which 27.5% were in the group with malnutrition risk and 52.7% were in the malnutrition group. There were statistical differences in the incidence of comorbid diabetes mellitus, body mass index (BMI), calf circumference,albumin, hemoglobin, and lymphocyte counts among the three groups. Further regression analysis suggested that combined diabetes, low calf circumference, and low albumin were independent risk factors for malnutrition. Conclusions The prevalence of malnutrition in elderly patients with COVID-19 was high, and nutritional support should be strengthened during treatment, especially for those with diabetes mellitus, low calf circumference, or low albumin.